PERAN SOSIAL DOMESTIK PEREMPUAN DALAM TAFSIR IBN KATSIR Sebuah Tinjauan Hermeneutik - Agustina, Arifah Millati (Ahkam: Jurnal Hukum Islam, 2016)
In understanding a text, of which focus is to find meaning in an open and comprehensive meaning, it needs to take into account not only literal but also moral ideas. The effort needs to be done to revive the destination stored in the one of the methods used by contemporary commentators is Hermeneutics. In this article the writer employs history analysis (Historically effected consciousness) and preunderstanding (Vorverstandnis) to understand the text. On the basis of the use of the theory of hermeneutics, the writer applies these theories in defining gender topics. Selection of gender topics is based on the consideration that many laws that do not contain moral ideas as a result of the reading of the text. The application of the two analyses above will result in objective interpretations as the meaning of text which is intended by its commentators. Kata kunci: Peran Sosial Domestik, Perempuan, Tafsir Ibn Katsir